Educational Attainment Better Increases the Chance of Breast Physical Exam for Non-Hispanic Than Hispanic American Women: National Health Interview Survey - Shervin Assari; Mohsen Bazargan (Baqiyatallah University of Medical Sciences, 2019)
Background: The Minorities' Diminished Returns (MDRs) theory suggests that the health effect of educational attainment is considerably smaller for members of racial and ethnic minority groups than for Whites. Objective: The current study explored the racial and ethnic differences in the association between educational attainment and Breast Physical Exam (BPE) among women in the U.S. Methods: The National Health Interview Survey (NHIS 2015) included 12 510 women who were Hispanic or non-Hispanic Black or White people. The independent variable was the level of educational attainment. The dependent variable was lifetime BPE. Age, region, marital status, and employment were the covariates. Race and ethnicity were the focal moderators. Logistic regressions were used for data analysis. Results: Overall, higher educational attainment was associated with higher odds of BPE, net of all confounders (odds ratio [OR]=1.11, 95% CI=1.09-1.13). Ethnicity showed a significant statistical interaction with educational attainment on BPE (OR=0.96, 95% CI=0.93-1.00), which was suggestive of a smaller effect of high education attainment on BPE for Hispanic than non-Hispanic women. The same interaction could not be found for the comparison of White and Black women (OR = 0.98, 95% CI =0.94-1.02). Conclusion: In line with other domains, non-Hispanic White women show a larger amount of health gain from their educational attainment than Hispanic women. It is not ethnicity or class but ethnicity and class that shapes how people engage in pro-health behaviors. This result may help hospitals and healthcare systems to better reduce health disparities in their target populations.